Advancement Flap for Removing Seborrheic Keratosis on the Helix of Ear: A Case Report - Ammarilis Murastami; Pratiwi Prasetya Primisawitri (HM Publisher, 2022)
Background: Seborrheic keratoses are benign intraepidermal neoplasms arising from epidermal keratinocytes. Age and UV exposure have a role in the course of the disease. Seborrheic keratosis consists of several types of cells, and transformation into various epithelial tumors originating from the same cell type can occur. Therefore, basal cell carcinoma may arise from the basaloid cells, which is the most commonly reported malignant neoplasm in seborrheic keratosis. Various treatment modalities are available to treat seborrheic keratoses. We report a case report of seborrheic keratosis resembling basal cell carcinoma and treated using surgical excision with the advancement flap technique. Case presentation: A 76-year-old man came with complaints of itchy, blackish-brown lumps on his left ear 3 months ago. On examination of the dermatological status on the helix auricula sinistra, there was a solitary nodule of blackish brown color with a diameter of 1cm x 1cm x 1cm and an ulcer with an uneven surface, well-defined, telangiectatic (+). An examination of the biopsy showed the results of seborrheic keratosis, keratotic type. The management of this case is excision with an advancement flap. Conclusion: Seborrheic keratosis is one of the most common benign skin tumors that occur in old age. Excision with an advancement flap showed good clinical improvement.